Imago urbis: imagined cities and cities’ representation (2012)
The article deals with the issue of the city as object depicted by art throughout history, and the art of drawing and representing as essential means for capturing the city and its architecture. It examines the metamorphoses of Imago Urbis and the art representing the urban from medieval times, the Renaissance and the Baroque, through Mannerism, Impressionism, Cubism, Futurism and Dada, as well as twentieth century art movements like Pop Art and Action Painting, among others. It also entails to the analysis modern techniques such as photography, film, video, digital technologies and current information networks and its effect upon the perception, representation and/or simulation of the city, which, according to the author, are ever more subjective and personal.